Assessment of the Success of Digital Signature and Stamp Implementation in the National Economic Rescue (PEN) Application System at Credit Insurance Companies in Indonesia - Nur Syamsuhadi; Sfenrianto Sfenrianto (Publikasi Indonesia, 2024)
Utilization technology in sector industry non-bank finance in Indonesia is increasingly widespread, including in the guarantee credit of state-owned companies. The company uses System Application Guarantee for transaction guarantee credit with produce Certificate Guarantee as proof of approval. The request can be active in the context of the COVID-19 pandemic and the Indonesian government's efforts to implement the company's National Economic Recovery (PEN) program guarantee. Implementation feature sign hand and digital stamp on the System Application PEN underwriting allows provision of document Guarantee Certificate in the form of legal and supportive softcopy restrictions contact physique during a pandemic. Study This aim is to measure the successful implementation features of the success models by Delone and McLean and analyze the connection between variables in research. The benefits cover assessment, evaluation, and strategy-based results evaluation using feature sign hand and digital stamp. Delone and McLean's original model was modified to eliminate variable intention to use. The research was conducted by analyzing the results of questionnaires from 108 officials' user systems throughout Indonesia. Process of data analysis using the method of Partial Least Square with device SMARTPLS software. Research results prove that quality systems will influence the satisfaction of future users who will be influential to benefit clean from the feature sign hand and digital stamp on the System Application PEN Guarante.